2018
DOI: 10.1002/jrs.5542
|View full text |Cite
|
Sign up to set email alerts
|

In situ Raman study of laser‐induced stabilization of reduced nanoceria (CeO2−x) supported on graphene

Abstract: This work demonstrates a novel approach to application of in situ Raman spectroscopy to study laser‐induced stabilization of reduced nanoceria (CeO2−x) supported on graphene—a promising nanocomposite for future development of nanomaterial‐enabled gas sensors or vital catalysts for hydrogenation of alcohols under anaerobic conditions. Structural stabilization of CeO2−x nanoparticles (NPs) on a graphene surface is evidenced by significant modification of Raman spectra—the appearance, increase in relative intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…In order to further explore the possibilities of TiS 2 applications in above‐mentioned examples, one needs to fully understand the fundamental properties of this material, including phonon properties. Phonon properties can be investigated using Raman spectroscopy, which has been proved to be an excellent tool for characterization of structural, thermal, optical, and electronic properties of layered materials . However, up to date, phonon properties (especially as a function of temperature) in titanium disulfide thin films are still poorly understood or unavailable.…”
Section: Calculated Parameters From Fit Of Equations  and To Temperamentioning
confidence: 99%
“…In order to further explore the possibilities of TiS 2 applications in above‐mentioned examples, one needs to fully understand the fundamental properties of this material, including phonon properties. Phonon properties can be investigated using Raman spectroscopy, which has been proved to be an excellent tool for characterization of structural, thermal, optical, and electronic properties of layered materials . However, up to date, phonon properties (especially as a function of temperature) in titanium disulfide thin films are still poorly understood or unavailable.…”
Section: Calculated Parameters From Fit Of Equations  and To Temperamentioning
confidence: 99%
“…The structure of the nanocomposites were characterized using micro‐Raman spectroscopy at appropriate experimental conditions 63 . The measurements were performed at room temperature in backscattering configuration using a triple Raman spectrometer T‐64000 Horiba Jobin‐Yvon, equipped with electrically cooled charge‐coupled device (CCD) detector and Olympus BX41 microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Their findings for the temperature dependence of the double resonance process in single‐layer MoS 2 can be extended to other classes of transition metal dichalcogenide materials. Nikolenko et al [ 86 ] reported on an in situ Raman study of laser‐induced stabilization of reduced nanoceria (CeO 2‐x ) supported on graphene. They conclude that by combining the structure conversion of nanoceria induced by electromagnetic radiation and its stabilization by the graphene support, this work provides a foundation for advanced concepts in the development of the next‐generation catalysts and sensors.…”
Section: Nanomaterialsmentioning
confidence: 99%